Green approach to synthesis polymer composites based on chitosan with desired linear and non-linear optical characteristics - Dyari M. Mamand; Sarkawt A. Hussen; Shujahadeen B. Aziz (Scientific Reports)
Abstract The current study used sustainable and green approaches to convey polymer composites with desired optical properties. The extracted green tea dye (GTD) enriched with ligands was used to synthesize zinc metal complexes. Green chitosan biopolymer incorporated with green synthesized metal complex using casting technique was used to deliver polymer composites with improved optical properties. The FTIR-ATR was used to identify the functional groups of the GTD, pure CS, and functional groups surrounding the synthesized zinc metal complex. Distinguished ATR bands were observed in green tea dye spectra, such as OH, C = O, and NH functional groups ascribed to various polyphenols. The ATR bands of the zinc metal complex compared to GDT established that GDT is crucial to capturing zinc cations and producing the Zn2+-metal complex. The broadness of the bands observed in CS-based composites inserted with the Zn2+- metal complex confirms strong interaction among the components of polymer composites. The XRD achievements confirm that CS films with different Zn2+- metal complex concentrations transferred to an amorphous composite. The XRD pattern of composite films establishes that the zinc metal complex scarified the crystalline phases of chitosan. Linear optical properties such as absorption, refractive index (n), and optical dielectric parameters were improved. The absorption edge of the composite’s films shifted to lower photon energies. Various models were used to determine the optical band gap. The band gap drops from $$\:5.3\:to\:≈\:\:1.5\:\text{e}\text{V}$$ when chitosan is loaded with a 36% Zn2+-metal complex. The Spitzer-Fan method is used to get the dielectric constant, and the Drude Lorentz oscillator model was used to calculate vital optical parameters, including N/m*, τ, and µ opt . The W-D single oscillator model was used to determine the E o and E d parameters. The values of optical moments (M −1 and M −3 ) were calculated with the help of the W-D model. The oscillator’s strength ( $$\:S_{0}$$ ) and wavelength ( $$\:{λ\:}_{0}$$ ) were determined via the Sellmeier model using the linear refractive index. The first-order nonlinear ( $$\:{χ\:}^{\left(1\right)}$$ ), second-order non-linear ( $$\:{χ\:}^{\left(2\right)}$$ ) and third-order nonlinear optical susceptibility ( $$\:{χ\:}^{\left(3\right)}$$ ) were determined for all the films.